Career Counseling and Constructivism: Elaboration of Constructs - McMahon, Mary; Watson, Mark (Nova Science Publishers, Incorporated, 2013)
Vocational guidance fits industrial societies and career counseling suits corporate cultures. However, neither guidance nor counseling seems to be the best practice for career intervention in the global economy of the information era. Thus, the emergence of career construction theory for comprehending vocational behavior and life-design interventions to assist people in choosing an adapting to work roles. This book examines and elaborates on the structural elements assembled into models of self-making, career constructing, and life designing.